Ergonomics of it outsourcing. development of a mathematical model to distribute functions among operators - Lavrov, Evgeniy; Pasko, Nadezhda; Krivodub, Anna; Barchenko, Natalia; Kontsevich, Valery (Eastern-European Journal of Enterprise Technologies, 2016)
The study suggests an optimization model for distributing a multitude of applications to implement digital control functions between operators of an IT outsourcing system. The importance of the developed model is determined by the increased complexity of human activities in automated systems and the need for prompt decisions in organizing execution of applications that are made at random times. We have proved that the task of optimizing activity selection algorithms can be achieved through describing the processes of human-computer interaction with the help of the functional network instruments that are accepted in the functional and structural theory of ergotechnical systems; ways of assigning functions to network operators can be perceived as alternatives. Furthermore, we have specified that the optimization task can be accomplished through using an activity graph and an event graph. We have studied the possibility of devising the most versatile model in the form of an event graph to formalize the tasks of distribution of functions. Each task is reduced to a linear programming problem. The suggestion can facilitate formation of decision support systems of operations managers or ergonomists-practitioners and significantly improve working conditions, operators’ motivation, and cost-effectiveness of system management by increasing the correctness and timeliness of implementing activity selection algorithms for the operating personnel.